Pemanfaatan Media Pembelajaran Berbasis Digital dimasa Pandemik - Adisel, Adisel; Azzara, Meishe Fitria; Sari, Chusnul Oktavia; Seftiansari, Annisa; Gusamba, Putama Nanda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the use of digital-based learning media during the COVID-19 pandemic. The method in this study uses the library study method. Literature Review is a method by collecting material, data and information from books, journals and articles related to the issues discussed. The results of the study, the use of digital-based media during the pandemic was fairly effective in teaching and learning activities. With technological advances that support the teaching and learning process, students will easily accept the material explained by the teacher through digital media. Digital media facilitates knowledge that teachers have never provided during face-to-face learning. Learning in digital media is very diverse so that learning has different nuances. This makes students motivated in every learning process they do during the pandemic. In conclusion, during the COVID-19 pandemic, digital media was chosen because it is more creative and innovative in delivering learning materials. The use of digital media is considered effective in overcoming the distance learning process and suppressing the spread of COVID-19. The benefits of digital-based learning provide direct benefits to students and teachers, especially in teaching and learning activities. Keywords: Digital, Learning Media, Covid 19 Pandemic